AKAD DAN TRANSAKSI JUAL BELI GABAH DALAM PRESPEKTIF EKONOMI ISLAM DI KABUPATEN SIDENRENG RAPPANG, SULAWESI SELATAN - Sirajuddin, Sirajuddin (Islamic Economics Program, Faculty of Islamic Economics and Business, 2021)
This study aims to determine how the contract and grain buying and selling transactions carried out by farmers and traders in the perspective of Islamic economics in Panca Rijang District. This type of research is descriptive qualitative using primary data. The data were obtained from interviews with farmers as sellers and traders as buyers in Panca Rijang District, Sidenreng Rappang Regency. This research uses a cultural approach. The results of the research obtained from interviews indicate that the trading practices carried out by farmers and traders in Panca Rijang District have fulfilled the elements of legal buying and selling. Analysis of the research data provides information that in general, farmers and traders in buying and selling unhulled rice have previously made a sale and purchase agreement with regard to the provisions of Islamic buying and selling.